Zur Ökologie der Trockentäler Bhutans - Würmli, Marcus (ERDKUNDE, 1977)
The author refers about personal observations made during a 3 months expedition in Bhutan. The article is a supplement to two papers published by Schweinfurth (1956, 1957). The valleys of Thimphu, Paro and Wang diphodrang - Punakha are dry valleys (Abb.1). A short description of the vegetation of the dry valleys is given. The sparse, dried up vegetation is anthropogenical. Originally the bottom and the slopes of the dry valleys were covered with a dry conifer forest mainly of Pinus rox burghii. The xerophilous vegetation of the dry valleys of Bhutan is similar to that of the alpine dry valleys (cf. Braun-Blanquet 1961). The biologically important factors of the climatically dry valleys are discussed.